Fuel property estimation and combustion process characterization : conventional fuels, biomass, biocarbon, waste fuels, refuse derived fuel, and other alternative fuels /: conventional fuels, biomass, biocarbon, waste fuels, refuse derived fuel, and other alternative fuels. (2018) - Kiang, Yen-Hsiung, 1947-
No abstract available